Comparative time-series multi-omics analyses suggest H1.2 involvement in anoxic adaptation and cancer resistance. - Juan Du; Weiqiang Liu; Meng Li; Zihao Li; Xuanjing Li; Yichen Dai; Gaoming Liu; Xiao Wang; Pingfen Zhu; Vadim N Gladyshev; Xuming Zhou (PLoS Biology)
The naked mole rat (NMR), Heterocephalus glaber, is known as the longest-lived rodent and is extraordinarily resistant to hypoxia and cancer. Here, both NMR embryonic fibroblasts (NEFs) and their mouse counterparts (MEFs) were subjected to anoxic conditions (0% O2, 5% CO2). A combination of comparative transcriptomics and proteomics was then employed to identify differentially expressed genes (DEGs). Notably, we observed distinct levels of histone H1.2 (encoded by HIST1H1C) accumulation between NEFs and MEFs. Subsequent mechanistic analyses showed that higher H1.2 expression in NEFs was associated with the lower expression of its inhibitor, PARP1. Additionally, we discovered that H1.2 can directly interact with HIF-1α PAS domains, thereby promoting the expression of HIF-1α through facilitating the dimerization with HIF-1β. The overexpression of H1.2 was also found to trigger autophagy and to suppress the migration of cancer cells, as well as the formation of xenograft tumors, via the NRF2/P62 signaling pathway. Moreover, an engineered H1.2 knock-in mouse model exhibited significantly extended survival in hypoxic conditions (4% O2) and showed a reduced rate of tumor formation. Collectively, our results indicate a potential mechanistic link between H1.2 and the dual phenomena of anoxic adaptation and cancer resistance.